COPING STRES, RESILIENSI PADA MAHASISWA TINGKAT AKHIR - Dwi Kusrini Alfa Wijianti; Fifin Dwi Purwaningtyas (PSIKOWIPA (Psikologi Wijaya Putra), 2020)
This research aims to find out if there is a link between stress coping and resilience in students who are compiling thesis at wijaya putra university surabaya, problems that occur in students who have difficulty and constraints in working on thesis caused by the many demands academically ranging from difficulty in finding titles, difficulty in finding research subjects, time constraints in the collection of reports etc. This research is a quantitative study with a type of descriptive research. The technique used in sampling is purposive sampling with the number of respondents 101 students who are composing thesis at Wijaya Putra University Surabaya. The instrument used is the scale of stress coping and resilience. The data retrieval tool in the form of stress coping questionnaire and resilience questionnaire is then applied to google forms. Data analysis technique using product moment correlation statistical technique with the help of SPSS 22 for windows program. From the analysis of the data the study obtained a correlation value between stress coping and resilience of 0.463 with a p of 0.000. This suggests that there is a significant correlation between coping stress and resilience. This means that the higher the stress coping, the higher the resilience in students who are compiling the thesis and vice versa the higher the resilience then the higher the coping stress in the student who is compiling the thesis.